2014
DOI: 10.14348/molcells.2014.2349
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor-1α Directly Regulates Nuclear Clusterin Transcription by Interacting with Hypoxia Response Elements in the Clusterin Promoter

Abstract: Differential transcription of the clusterin (CLU) gene yields two CLU isoforms, a nuclear form (nCLU) and a secretory form (sCLU), which play crucial roles in prostate tumorigenesis. Pro-apoptotic nCLU and anti-apoptotic sCLU have opposite effects and are differentially expressed in normal and cancer cells; however, their regulatory mechanisms at the transcriptional level are not yet known. Here, we examined the transcriptional regulation of nCLU in response to hypoxia. We identified three putative hypoxia res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…The hypoxia‐inducible factor (HIF) 1, a heterodimer of HIF‐1β (constitutively expressed), and HIF‐1α (O 2 ‐regulated), is a primary factor for these adapting mechanisms (Ke and Costa, ). Hypoxia up‐regulates CLU expression in kidney cells (Alnasser et al, ) or tenocytes (Millar et al, ), and HIF‐1 binding hypoxia response elements are identified in CLU gene promoter (Park et al, ), suggesting that up‐regulation of CLU may be part of survival mechanisms of cells in hypoxia. Indeed, our previous study has demonstrated that CLU expression is required for activation of prosurvival autophagy in the kidneys with IRI, and in cultured kidney cells in hypoxia that is associated with UPR (Alnasser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxia‐inducible factor (HIF) 1, a heterodimer of HIF‐1β (constitutively expressed), and HIF‐1α (O 2 ‐regulated), is a primary factor for these adapting mechanisms (Ke and Costa, ). Hypoxia up‐regulates CLU expression in kidney cells (Alnasser et al, ) or tenocytes (Millar et al, ), and HIF‐1 binding hypoxia response elements are identified in CLU gene promoter (Park et al, ), suggesting that up‐regulation of CLU may be part of survival mechanisms of cells in hypoxia. Indeed, our previous study has demonstrated that CLU expression is required for activation of prosurvival autophagy in the kidneys with IRI, and in cultured kidney cells in hypoxia that is associated with UPR (Alnasser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…2A). CoCl 2 is a well-described hypoxiamimetic agent [7,12,14] but also activates the nuclear transcription factor NF-κB [15]. There are two putative κB elements within the FABP3 gene at À 834 and À 825 bp that are presumably responsible for this increase in luciferase activity (data not shown).…”
Section: Hypoxia Induces Fabp3 Expressionmentioning
confidence: 96%
“…We concluded that the region from À 1315 to À 648 bp of FABP1 responds predominantly to HIF-1α. In other studies the number of functional HRE within the gene being tested is proportional to the intensity of the luciferase activity [12].…”
Section: Functional Hypoxia-response Element(s) In the Human Fabp1 Genementioning
confidence: 99%
“…58 Recent studies showed that nuclear clusterin transcription could be directly regulated by HIF-1α. 59 Our previous study showed that reactive oxygen species (ROS) such as H 2 O 2 level in choroid of OIR is significantly higher ( p < 0.01) than that in controls and may lead to high H 2 O 2 level in retinas of OIR. 17 Thus, the elevated STAT1 here may play a similar role of response to intracellular ROS in retinas of OIR as these in human diseases.…”
Section: Resultsmentioning
confidence: 97%